Faktor yang Mempengaruhi Prestasi Belajar Siswa pada Pembelajaran PKN di MIS Fajar Shiddiq Kota Medan Marelan - Abdulgani Jamora Nasution; Nurazmi Br Siregar; Syakira Anandia; Khoirun Nisa; Wiryo Sastro Handoyo (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This study aims to: describe the factors that influence student achievement, determine student learning outcomes. This type of research is qualitative, namely to determine how to find, collect, process and analyze data from the research. The sample of this research was fourth grade students at MIS FAJAR SHIDDIQ, totaling 32 people. Data collection methods used are observation, interviews and documentation studies. Data on factors that influence learning outcomes are collected using observation sheets and interview guidelines. The results of this study at MIS FAJAR SHIDDIQ show that the factors that influence student achievement in grade IV students are influenced by internal (inside) and external (external) factors. Internal factors include physical factors and psychological factors. Physical factors such as state of health, state of the body. And psychological factors such as attention, interest, talent, and readiness. While external factors, namely school factors such as curriculum, teaching methods, interaction between students, discipline at school, learning tools, the condition of the building, and the library. However, in this study centered on internal factors or within the student. Keywords: PPKN, Learning Achievement, Factors